RESPON PERTUMBUHAN TEBU (SACCHARUM OFFICINARUM L.) PADA KEDALAMAN JURINGAN DAN DOSIS PUPUK P YANG BERBEDA - Ivanovich Rahman; Rina Ekawati; Anna Kusumawati (AGROISTA : Jurnal Agroteknologi, 2022)
Sugarcane (Saccharum officinarum) can grow well in soil and environmental conditions that are under growing requirements and accompanied by good management also. The land is a natural resource with a permanent nature, while the human need for land continues to increase and the high need for nutrients in sugarcane causes a rapid decline in nutrients in the soil, especially monoculture sugarcane. This study aims to determine the effect of the response of sugarcane growth on the depth of juringan and the dosage of P fertilizer. The experiment was carried out at Wedomartani Experimental Garden, Ngemplak, Sleman, Yogyakarta from January to March (3 months). The experiment used a factorial randomized block design. The first factor is the depth of the rod with three treatments, namely: the depth of the rod 15 cm (K0), the depth of the rod 30 cm (K1), and the depth of the rod 45 cm (K2). The second factor was the dosage of P fertilizer with three treatments, namely: without P fertilizer (P0), P fertilizer 13 g / seed (P1), and P fertilizer 22 g / seed (P2). Six treatment combinations were repeated three times so that there were 27 experimental units. Each experimental unit consisted of two plants, so there were a total of 54 plants. The results showed that there was no interaction between the different depths of the net and the dosing of P fertilizer on all observed variables. Application of different P fertilizers had a single effect on plant height, number of tillers, and leaves. Application of P fertilizer (22 g / seed) resulted in higher plant height and number of tillers compared to without P fertilizer. Keywords: monoculture, phosphorus, sugarcane, production.